Ressonância na fase isotrópica de cristais líquidos - Oliveira, Davi Antunes de (2001)
In this work we have studied the birefringence induced by mechanical vibrations within a liquid crystals isotropic phase. The resonance in that lyotropic liquid crystal isotropic phase occurs from 0.2 Hz to 1K Hz. We have found a natural frequency aobut 20 Hz which has no dependence of temperature and relative concentration of the mixture. The decay time of the resonance peaks, td was experimentally obtained and its values have an order of 1s, for 120 Hz, and 10-1 for both 20 Hz and 60 Hz. The behavior of td as a function of temperature indicates the existences of an induced "nematic" phase in the isotropic phase at stationary regime. The birefringence induced by mechanical vibrations in the isotropic phase of a lyotropic liquid crystal is of the order of 10-4.